Involvement of mechanosensitive ion channels in the effects of mechanical stretch induces osteogenic differentiation in mouse bone marrow mesenchymal stem cells. Issue 1 (27th June 2020) - Wu, Tianyi; Yin, Fuli; Wang, Nan; Ma, Xin; Jiang, Chaolai; Zhou, Lihui; Zong, Yang; Shan, Haojie; Xia, Wenyang; Lin, Yiwei; Zhou, Zubin; Yu, Xiaowei
Abstract: Bone marrow mesenchymal stem cells (BMSCs) can be induced to process osteogenic differentiation with appropriate mechanical and/or chemical stimuli. The present study described the successful culture of murine BMSCs under mechanical strain. BMSCs were subjected to 0%, 3%, 8%, 13%, and 18% cyclic tensile strain at 0.5 Hz for 8 hr/day for 3 days. The expression of osteogenic markers and mechanosensitive ion channels was evaluated with real‐time reverse transcription‐polymerase chain reaction (RT‐PCR) and western blot. The expression of alkaline phosphatase (ALP) and matrix mineralization were evaluated with histochemical staining. To investigate the effects of mechanosensitive ion channel expression on cyclic tensile strain‐induced osteogenic differentiation, the expression of osteogenic markers was evaluated with real‐time RT‐PCR in the cells without mechanosensitive ion channel expression. This study revealed a significant augment in osteogenic marker in BMSC strained at 8% compared to other treatments; therefore, an 8% strain was used for further investigations. The ALP expression and matrix mineralization were enhanced in osteogenic induced BMSCs subjected to 8% strain after 7 and 14 days, respectively. Under the same conditions, the osteogenic marker and mechanosensitive ion channel expression were significantly promoted. However, the loss function of mechanosensitive ion channels resulted in the inhibition of osteogenic marker expression. This study demonstrated that strain alone can successfully induce osteogenic differentiation in BMSCs and the expression of mechanosensitive ion channels was involved in the process. The current findings suggest that mechanical stretch could function as efficient stimuli to induce the osteogenic differentiation of BMSCs via the activation of mechanosensitive ion channels. Abstract : The current findings suggest that mechanical stretch could function as efficient stimuli to induce osteogenic differentiation of bone marrow mesenchymal stem cells via the activation of mechanosensitive ion channels.